Seizure outcome following medical treatment of mesial temporal lobe epilepsy: Clinical phenotypes and prognostic factors - Igor Kuzmanovski; Emilija Cvetkovska; Marija Babunovska; Gordana Kiteva Trencevska; Biljana Kuzmanovska; Bojan Boshkovski; Rozalinda Isjanovska (Elsevier BV, 2016)
Surveys on mesial temporal lobe epilepsy (MTLE) repeatedly demonstrate that seizures are commonly resistant to antiepileptic drugs (AED), but patients usually came from third-level epilepsy centers, making the medically refractory population larger. The aim of our study is to evaluate patterns of seizure control and prognostic factors of general population of MTLE patients observed in clinical practice.